2021
DOI: 10.1097/wco.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Updates on management of headache in women and transgender women

Abstract: Purpose of review Gender differences exist in headache disorders. A greater understanding of the role of hormones in headache can help the clinician better approach and manage common primary headache disorders. Recent findings Recent studies highlight differences in how migraine and cluster headache present in women and men. Updates to the ongoing debate of how to manage the use of hormones in women with migraine, especially with aura, have been well re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some of these associations have long been demonstrated in the general population; this study confirms that the same is true in the workplace. The higher prevalence in women is an established fact in the literature [ 74 ]. Conclusive studies have associated bereavement with frequent and severe headaches [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these associations have long been demonstrated in the general population; this study confirms that the same is true in the workplace. The higher prevalence in women is an established fact in the literature [ 74 ]. Conclusive studies have associated bereavement with frequent and severe headaches [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study revealed that women were independent predictors of the occurrence of ischemic stroke-related headaches, which is consistent with the results of a previous study on migrainous infarction [ 52 ]. Primarily, this finding may be related to the endocrine hormones and physiological protein regulation in women [ 53 ]. Second, women are more susceptible to mood swings than men and are especially more likely to experience negative emotions, such as anxiety and irritability, because of an illness.…”
Section: Discussionmentioning
confidence: 99%
“…Cisgendered women experience higher rates of migraine, often two to three times that of cisgendered men, 51 whereas cisgendered men experience cluster headaches up to five times that of cisgendered women. 52 The effects of sex hormones are complex, with both direct effects on higher-order functional neural networks and vascular structures, as well as indirect effects through genomic alterations and neurotransmitter signaling. 53 Animal and laboratory models 54 have shown that estrogen increases central opioid tone, decreases serotonin, activates the trigeminovascular system, modulates levels of inflammatory mediators including calcitonin gene-related peptide, and increases susceptibility to cortical spreading depolarization, the mechanism thought to cause auras.…”
Section: Hormonesmentioning
confidence: 99%